1985
DOI: 10.1159/000233780
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Heterogeneity in Response to Cholinergic Stimulation

Abstract: Mast cell heterogeneity in response to acetylcholine has been evidentiated by the virtual lack of sensitivity or by the full reaction to nanomolar concentrations of acetylcholine, observed in samples of serosal mast cells isolated from the same animal species. The incubation with IgE of isolated rat mast cells renders the originally heterogeneous response homogeneous, the release of histamine evoked by acetylcholine being proportional to the IgE concentration. The histamine release induced by acetylcholine is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…In addition to bronchial smooth muscle cells, endothelial [19], epithelial [20], neutrophils [21], lymphocytes [22], mast cells [23] monocytes and macrophages [24] have been reported to possess muscarinic acetylcholine receptors. Furthermore, the data available do not distinguish whether the mediator response in BAL fluid is a direct effect of methacholine or of bronchoconstriction itself.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bronchial smooth muscle cells, endothelial [19], epithelial [20], neutrophils [21], lymphocytes [22], mast cells [23] monocytes and macrophages [24] have been reported to possess muscarinic acetylcholine receptors. Furthermore, the data available do not distinguish whether the mediator response in BAL fluid is a direct effect of methacholine or of bronchoconstriction itself.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that the earliest description of potential cholinerergic regulation of mast cells was not an inhibitory action at the nicotinic receptors but an activation and induction of degranulation by acetylcholine acting at the muscarinic receptors [107,108]. Mannaioni and colleagues [107] reported that histamine secretion from rat mast cells occurs in the presence of nanomolar concentrations of acetylcholine, an effect that was competitively blocked by atropine.…”
Section: Cholinergic Neuronsmentioning
confidence: 99%
“…However, other studies failed to show any effect of acetylcholine on rat mast cell degranulation [109,110]. Masini et al [108] went on to identify heterogeneity in response to acetylcholine with the virtual lack of sensitivity or by the full reaction to nanomolar concentrations of acetylcholine, observed in samples of serosal mast cells isolated from rats. The incubation with isolated rat mast cells with IgE induced a homogenous 'responder' population, with acetylcholine-induced histamine release proportional to the IgE concentration.…”
Section: Cholinergic Neuronsmentioning
confidence: 99%
“…3A). Mast cells have AChRs, and degranulation of mast cells is regulated by these receptors111213. Destruction of the skin barrier on day seven may have involved the degranulation of mast cells via cholinergic signals.…”
Section: Discussionmentioning
confidence: 99%